Framework Enhancement for Common Public Radio Interface in SBTS - V, Anuradha; R, Shankar (International Journal of Engineering and Technology, 2018)
There is a rapid growth of mobile users so there are developing more number of features by a service provider to support more number of mobile users. The Common Public Radio Interface (CPRI) is an interface between the Radio Equipment Controller (REC) and Radio Equipment (RE) to support more number of users. This simplifies the overall architecture of radio base station. The radio base station is centralized and the radio heads are distributed in the environment. This radio heads supports the more number of users. The main aim of CPRI is to divide the packets into number of frames. The radio frame is divided into the hyper frames and this hyper frame is divided into the number of basic frame in which each basic frame is supported up to 16 words totally it supports up to 6,144 megabytes per second.
Keywords: CPRI; REC; RE; Radio Frames and Hyper Frame.